Promoting the general welfare new perspectives on government performance - Gerber, Alan S.; Patashnik, Eric M.; Brookings Institution; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2006)
"Analyzes government's ability to "promote the general welfare" in the areas of health, transportation, housing, and education. Then examines two tools to improve policy design: information markets and laboratory experiments. Concludes by asking how Congress, the party system, and federalism affect government's ability to solve important social problems"--Provided by publisher.
Government performance : missing opportunities to solve problems / Alan S. Gerber and Eric M. Patashnik -- Policy analysis in representative democracy / David L. Weimer and Aidan R. Vining -- Sham surgery : the problem of inadequate medical evidence / Alan S. Gerber and Eric M. Patashnik -- Urban transportation / Clifford Winston -- Achieving fundamental housing policy reform / Edgar O. Olsen -- Fixing special education / Jay P. Greene -- Decision markets for policy advice / Robin Hanson -- An experimental basis for public policy initiatives / Charles A. Holt, William M. Shobe, and Angela M. Smith -- Can Congress serve the general welfare? / Sarah A. Binder -- Congress as problem solver / David R. Mayhew -- Parties as problem solvers? / Morris P. Fiorina -- Taking the Brandeis metaphor seriously : policy experimentation within a federal system / Mark Carl Rom -- The states as a laboratory : legal innovation and state competition for corporate charters / Roberta Romano -- Two perspectives on governmental underperformance / Eugene Bardach.
Papers originally presented at a conference held at the University of Virginia in November 2004.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Public welfare administration -- United States -- Evaluation -- Congresses; Public administration -- United States -- Evaluation -- Congresses; United States -- Social conditions -- 1980- -- Congresses; United States -- Politics and government -- 2001-2009 -- Congresses; Electronic books